Laparoscopic repair of paraesophageal hiatus hernia in infancy - Kundal Anjani; Zargar Noor; Krishna Anurag (Wolters Kluwer Medknow Publications, 2008)
Paraesophageal hiatus hernia (PEHH) is an uncommon type of diaphragmatic hernia in the pediatric age group. Two patients aged 5-months and 8-months presented with respiratory symptoms and underwent a laparoscopic repair. Preoperative assessment included chest x-ray and CT scan. We suggest that laparoscopic repair of PEHH in infants is safe and preferred mode of the treatment.